Produksi Barbel Cor 5 kg, Panjang 23 cm, Diameter Pegangan 3 cm, Kapasitas 2 Biji/Jam - Kaulan Syadid; Syamsul Hadi; Moch Rexy Satrianto; Muhammad Raditya Cantona; Rio Citra Kusuma (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Sports equipment Barbells made of cement concrete require more volume than barbells made of cast iron as a problem faced. The production goal is to produce a 5 kg barbell, measuring a total length of 23 cm, a handle length of 13 cm, a diameter of 3 cm and a load diameter of 9 cm. Production methods include: barbell design; sand mold design; making sand molds for one print to obtain 2 units; preparation of labor; preparation of raw materials for cast iron, coke, limestone, ladel / carrier kowi, pouring molten cast iron into the mold, and adhesive / binder; melting cast iron; pouring cast iron into the heated mold; dismantling the mold and cutting the pouring bowl and riser; checking the weight of the barbell and its correction; finishing with spray paint according to the order; and checking the quality, dimensions, and packaging. The production results are in the form of a barbell weighing 5 kg 20 g with a total length of 23 cm and a handle diameter of 3 cm x 13 cm, a barbell load diameter of 9 cm, a total production cost of IDR 50,000 / unit, and a production duration of 30 minutes / unit which implies that the production of barbells is feasible to be carried out by medium to large industries / businesses, because it requires sufficient capital, especially for the cost of the Kupola furnace.